PERAN LEMBAGA PENDIDIKAN DALAM PENINGKATAN KUALITAS GURU PENDIDIKAN ANAK USIA DINI - Umu Da'watul Choiro; Agus Fathoni Prasetyo (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
The big problem that is still faced by national education until now is the issue of quality, effectiveness and efficiency of education. It has become a common understanding that the issue of educators is far more important than the problems of curriculum and other educational components. With the following important aspects educational institutions can play a role in improving the quality of their educators, including: (1) salaries and welfare standards that are appropriate for their lives, (2) qualification standards, (3) competency standards and efforts to improve them, (4) certification system for educators and educators and professional transfers that do not meet competency standards, (4) honest and transparent selection / recruitment, (5) career development standards, (6) preparation of prospective educators and education personnel in line with competency standards, and more emphasizing practice and with strong theory, (7) education and training system in professional training and education institutions and (8) empowering professional development organizations.